(untitled) (World Bulletin of Social Sciences, 2022)
The aim of this research is to identify the impact of the commitment to achieve a result and the commitment to exert great care on building the rules of contractual responsibility. On the personal error of the lessor and the lessee, and all of this explains the impact that each of these two obligations left on the basis of contractual liability for the actions of others in the lease contract, by following the descriptive and analytical approaches and the comparative legal approach. In the end, some conclusions and recommendations were reached